2021
DOI: 10.1136/bmjopen-2021-050159
|View full text |Cite
|
Sign up to set email alerts
|

Association of long-term exposure to PM2.5 with hypertension prevalence and blood pressure in China: a cross-sectional study

Abstract: ObjectiveEvidence of the effects of long-term fine particulate matter (PM2.5) exposure on hypertension and blood pressure is limited for populations exposed to high levels of PM2.5. We aim to assess associations of long-term exposure to PM2.5 with hypertension prevalence and blood pressure, and further explore the subpopulation differences and effect modification by participant characteristics in these associations in China.MethodsWe analysed cross-sectional data from 883 827 participants aged 35–75 years in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
1
4
0
1
Order By: Relevance
“…Notably, malesexhibited a higher susceptibility to long-term exposure to PM 2.5 with an attributable fraction of hypertension reaching 3.6% (95% CI, 3.4 to 3.7), compared to only 0.5% (95% CI, 0.3 to 0.6) in females [ 33 ]. A separate cross-sectional study involving nearly 1 million Chinese patients investigated the correlation between long-term exposure to PM 2.5 and hypertension, revealing that advanced age, male, and obesity exhibit heightened susceptibility to PM 2.5 exposure consistent with our findings [ 34 ]. However, Curto et al's study investigating the association between PM 2.5 and hypertension among adult males and females in 28 urban areas of India revealed that males exhibited lower susceptibility to PM 2.5 , while females showed a positive correlation between exposure to PM 2.5 and hypertension.…”
Section: Discussionsupporting
confidence: 86%
“…Notably, malesexhibited a higher susceptibility to long-term exposure to PM 2.5 with an attributable fraction of hypertension reaching 3.6% (95% CI, 3.4 to 3.7), compared to only 0.5% (95% CI, 0.3 to 0.6) in females [ 33 ]. A separate cross-sectional study involving nearly 1 million Chinese patients investigated the correlation between long-term exposure to PM 2.5 and hypertension, revealing that advanced age, male, and obesity exhibit heightened susceptibility to PM 2.5 exposure consistent with our findings [ 34 ]. However, Curto et al's study investigating the association between PM 2.5 and hypertension among adult males and females in 28 urban areas of India revealed that males exhibited lower susceptibility to PM 2.5 , while females showed a positive correlation between exposure to PM 2.5 and hypertension.…”
Section: Discussionsupporting
confidence: 86%
“…Результаты показали, что чем больше часов работы в день, в том числе в сидячем положении (как в группе сравнения), тем выше вероятность ожирения и СД 2-го типа [3,9,35]. По мере увеличения ИМТ человека увеличивается количество дней временной нетрудоспособности, медицинских обращений в медицинские организации по поводу ХНИЗ [35,36,37].…”
Section: Discussionunclassified
“…48 Likewise, in Spanish adults, higher exposure to PM 2.5 and PM 10 was significantly related to an increased incidence of hypertension 49 and similar in cohorts of Chinese children and adolescents 50 and adults. 51 In a Chinese cohort exposed to extreme levels of air pollution, a relationship between black carbon (an anthropogenic surrogate of fossil fuel combustion) and ambulatory blood pressure was demonstrated: a 1 µg increase in black carbon during the previous 10 hours was associated with an increase in systolic blood pressure of 0.53 mm Hg and diastolic blood pressure of 0.37 mm Hg (95% CI, 0.17–0.89 and 0.10–0.65 mm Hg, respectively), 52 which also caused heart rate variability suggestive of sympathetic dominance. 52 In India, higher levels of PM 2.5 exposure were associated with a greater risk of incident hypertension and increased systolic blood pressure.…”
Section: Recent Epidemiological/observational Evidence For Adverse Ef...mentioning
confidence: 99%